Analysis of the Effect of Financial Literacy on Saving Interest of PT Originalnest Medan Employees - Roma Ito Aritonang; Maya Macia Sari (Journal of Research in Social Science and Humanities, 2024)
This study was conducted to determine and analyze the effect of financial literacy on saving interest. The measurement of financial literacy used in this study is financial knowledge and financial attitudes. The location of this research was conducted at PT Originalnest Pancing Medan. This type of research is descriptive research with a quantitative approach. The research method is multiple linear regression analysis with a sample of 100 employees. The results showed that partially the financial knowledge variable had no effect on employee interest in saving. Financial attitude variables have a significant positive effect on employee interest in saving. While simultaneously the financial knowledge and financial attitude variables have a significant positive effect on the dependent variable of employee saving interest.